BS EN 2876. Aerospace series. Nuts, hexagon, plain, reduced height, normal across flats, in aluminium alloy, anodized. Classification: 450 MPa (at ambient temperature)/120 °C. (7th December 2020) - British Standards Institution
No abstract available